International Monetary Policy Coordination - Michael Carlberg (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2005)
This paper studies the international coordination of monetary policies in the world economy. It carefully discusses the process of policy competition and the structure of policy cooperation. As to policy competition, the focus is on monetary competition between Europe and America. Similarly, as to policy cooperation, the focus is on monetary cooperation between Europe and America. The spillover effects of monetary policy are negative. The policy targets are price stability and full employment.
urn:nbn:de:gbv:705-opus-16574
Keywords: F42; F41; F33; E52; 330; European Monetary Union; International Policy Coordination; Monetary Policy; Internationale Währungspolitik; Geldpolitik; Konjunkturzusammenhang; Theorie; USA; EU-Staaten